Upaya Guru IPS dalam Mengembangkan Karakter Tanggung Jawab Siswa - Daneang, Syahrul; Citra, Desy Eka; Gilang, M. Ilham (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to describe the Role of social studies teachers in developing students' responsible character in social studies learning at SMP Negeri 25 Bengkulu City. I also learned about the obstacles social studies teachers face in improving students' honest character, discipline, and responsibility at SMP Negeri 4 South Bengkulu. This research includes a qualitative approach, and this type of research uses a purposive sampling method. Researchers collect and obtain data through interviews, observation, and documentation. The results of this research can be explained as follows: the Role of social studies teachers in developing responsible character is as a motivator, corrector, guide, and initiator. Meanwhile, the obstacles for social studies teachers in developing students' responsible character are: 1) family factors. Families often do not pay attention to children's behavior, so children fall into the wrong environment. 2) the friend factor: sometimes children cannot choose which friends are good and which are misleading. 3) environmental factors that do not always support maximum character formation. Keywords: Social Studies Teacher, Developing character, Role